Simultaneous Determination Of Sodium Benzoate And Sodium Cyclamate In Soft Drink Using High Performance Liquid Chromatography - Ariya Wijaya Putra; Asri Darmawati; Juniar Mochtar (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2016)
Background: Sodium benzoate and sodium cyclamate are foods additives generally used as preservative and artificial sweeteners, respectively. Monitoring of sodium benzoate and sodium cyclamate need appropriate analytical method. Objective: The main objective of this study was to gain the optimum conditions for simultaneous determination of sodium benzoate and sodium cyclamate in soft drink by High Performance Liquid Chromatography. Methods: Measurement of the additives was performed in µ-Bondapak RP18 column using methanol:phosphate buffer of pH 4 (42:58) as mobile phase with flow rate of 1 mL/minute. Results: It has shown that correlation coefficients (r) of sodium benzoate and sodium cyclamate was 0.9997 and 0.9991 respectively. Recoveries of the two analyst were acceptable. Conclusions: Five out of nine samples tested contained sodium cyclamate higher than the recommended concentration. All sodium benzoate containing samples were within the recommended concentration.